Effect of inhaling cymbopogon martinii essential oil and geraniol on serum biochemistry parameters and oxidative stress in rats - Andrade, Bruna Fernanda Murbach Teles [UNESP]; Braga, Camila Pereira [UNESP]; Santos, Klinsmann Carolo dos [UNESP]; Barbosa, Lidiane Nunes [UNESP]; Rall, Vera Lúcia Mores [UNESP]; Sforcin, José Maurício [UNESP]; Fernandes, Ana Angélica Henrique [UNESP]; Fernandes Júnior, Ary [UNESP] (Wiley, 2014)
The effects of the inhalation of Cymbopogon martinii essential oil (EO) and geraniol on Wistar rats were evaluated for biochemical parameters and hepatic oxidative stress. Wistar rats were divided into three groups (n = 8): G1 was control group, treated with saline solution; G2 received geraniol; and G3 received C. martinii EO by inhalation during 30 days. No significant differences were observed in glycemia and triacylglycerol levels; G2 and G3 decreased (P < 0.05) total cholesterol level. There were no differences in serum protein, urea, aspartate aminotransferase activity, and total hepatic protein. Creatinine levels increased in G2 but decreased in G3. Alanine aminotransferase activity and lipid hydroperoxide were higher in G2 than in G3. Catalase and superoxide dismutase activities were higher in G3. C. martinii EO and geraniol increased glutathione peroxidase. Oxidative stress caused by geraniol may have triggered some degree of hepatic toxicity, as verified by the increase in serum creatinine and alanine aminotransferase. Therefore, the beneficial effects of EO on oxidative stress can prevent the toxicity in the liver. This proves possible interactions between geraniol and numerous chemical compounds present in C. martinii EO.